Um hipermídia sobre fases da lua para o ensino de astronomia a distância - Costa, José Roberto de Vasconcelos (2011)
The interdisciplinary nature of Astronomy makes it a field of great potential to explore various scientific concepts. However, studies show a great lack of understanding of fundamental subjects, including models that explain phenomena that mark everyday life, like the phases of the moon. Particularly in the context of distance education, learning of such models can be favored by the use of technologies of information and communication. Among other possibilities, we highlight the importance of digital materials that motivate and expand the forms of representation available about phenomena and models. It is also important, however, that these materials promote the explicitation of student's conceptions, as well as interaction with the most central aspects of the astronomical model for the phenomenon. In this dissertation we present a hypermedia module aimed at learning about the phases of the moon, drawn from an investigation on the difficulties with the subject during an Astronomy course for teaching training at undergraduate level at UFRN. The tests of three semesters of course were analyzed, taking into account also the alternative conceptions reported in the literature in astronomy education. The product makes use of small texts, questions, images and interactive animations. Emphasizes questions about the illumination of the Moon and other bodies, and their relationship to the sun, the perception from different angles of objects illuminated by a single source, the cause of the alternation between day and night, the identification of Moon's orbit around the Earth and the occurrence of the phases as a result of the position of observing it, and the perception of time involved in the phenomenon. The module incorporated considerations obtained from interviews with students in two poles where its given presential support for students of the course, and subjects from different pedagogical contexts. The final form of the material was used in a real situation of learning, as supplementary material for the final test of the discipline. The material was analyzed by 7 students and 4 tutors, among 56 users, in the period in question. Most students considered that the so called "Lunar Module" made a difference in their learning, the animations were considered the most prominent aspect, the images were indicated as stimulating and enlightening, and the text informative and enjoyable. The analysis of learning of these students, observing their responses to issues raised at the last evaluation, suggested gains in key aspects relating to the understanding of the phases, but also indicates more persistent difficulties. The work leads us to conclude that it is important to seek contributions for the training of science teachers making use of new technologies, with attention to the treatment of computer as a complementary resource. The interviews that preceded the use of the module, and the way student has sought the module if with questions and/or previous conflicts - established great difference in the effective contribution of the material, indicating that it should be used with the mediation of teacher or tutor, or via strategies that cause interactions between students. It is desirable that these interactions are associated with the recovery of memories of the subjects about previous observations and models, as well as the stimulus to new observations of phenomena